LEGAL ASPECTS OF THE ENVIRONMENTAL PROTECTION POLICY IN THE REPUBLIC OF POLAND. SELECTED ISSUES - Kamiński, Paweł; Radziwon-Kamińska, Ilona; Targońska, Agnieszka (Management and Administration Journal, 2020)
Environmental protection policy is a multi-faceted issue which interests researchers in different branches of knowledge. The implementation of solutions of the environmental protection may take different forms among which are legal instruments. One of those legal instruments is the environmental protection policy. The aim of this article is to analyse this policy and to evaluate its functioning in the Republic of Poland as one of the public policies. Furthermore, a crucial part of this article is to define the environmental protection policy, national environmental policy and its legal bases. What is more, the article will present the analysis of purposes, directions and areas included in the Polish National Environmental Policy - 2030. To make this analysis complete it is required to indicate symptoms of the sustainable development in the environmental protection policy. As a main tool of consideration, the dogmatic-legal method, has been used. The analysis of the main topic consists of legal acts and literature on the subject (containing Polish and foreign scientific publications).